Disclaimer Labels Used in Ads: An Eye-Tracking Study Exploring Body Dissatisfaction and Physical Appearance Comparison Among University Students - G. Motif Atar; Bilge İspir; Gülcan Şener (Türkiye İletişim Araştırmaları Dergisi)
The necessity of having a perfect beauty created with advertisements has negative impacts on young people.Advertisements usually feature very slim models and their digitally altered, airbrushed and trimmedphotos. Ideal beauty is created by retouching and changing digitally existing images. People compare theirbodies to the perfect bodies in advertisements. Especially young women and men compare these perfectbodies with their own bodies and experience dissatisfaction. This may lead to anxiety, depression and lackof self-confidence in people who are not ideally sized.Since ideal beauty influences the audience, the physical attractiveness of people starring in advertisementsis one of the subjects worth stressing. With an experimental design, the eye movements of young female(40) and male (40) participants were recorded using the eye-tracking method. During this process,participants saw advertisements with and without disclaimer labels. The male participants saw the printadvertisement which included the male model, and the female participants saw the print advertisementwhich included the female model. At the end of the experiment, the Body Dissatisfaction Scale (BDS)and the Physical Appearance Comparison Scale (PACS) were applied to the participants. The relationshipbetween the participants’ levels of body dissatisfaction and physical appearance comparison and their focuson Areas of Interest (AOI) in stimulated and non-stimulated advertising was revealed. The findings of thestudy showed that body dissatisfaction is high among young people and the level of body dissatisfaction didnot affect more attention to any part of the model (body and face).